Natural fibers for hydrogels production and their applications in agriculture (2017)
This paper presents a review on hydrogels applied to agriculture emphasizing on the use of natural fibers. The objectives were to examine, trends in research addressed to identify natural fibers used in hydrogels development and methods for modifying natural fibers, understand factors which determine the water retention capacity of a hydrogel. Consequently, this paper shows some methodologies used to evaluate the hydrogels efficiency and to collect in tables, relevant information in relation to methods of natural fibers modification and hydrogel synthesis. It was found that previous research focused on hydrogels development processed with biodegradable polymers such as starch, chitosan and modified natural fibers, cross-linked with potassium acrylate and acrylamide, respectively. In addition, current researches aimed to obtaining hydrogels with improved properties, which have allowed a resistance to climatic variations and soil physicochemical changes, such as pH, presence of salts, temperature and composition. In fact, natural fibers such as sugarcane, agave fiber and kapok fiber, modified with maleic anhydride, are an alternative to obtain hydrogels due to an increasing of mechanical properties and chemically active sites. However, the use of natural nanofibers in hydrogels, has been a successful proposal to improve hydrogels mechanical and swelling properties, since they give to material an elasticity and rigidity properties. A hydrogel efficiency applied to soil, is measured throughout properties as swellability, mechanical strength, and soil water retention. It was concluded that hydrogels, are an alternative to the current needs for the agricultural sector.